Amyloid goiter - A rare case report and literature review. (September 2020) - Lari, Eisa; Burhamah, Waleed; Lari, Ali; Alsafran, Salman; Ismail, Ali
Abstract: Introduction: Amyloid goiter is a rare presentation of thyroid swelling, which occurs with either primary or secondary amyloidosis. This condition must be differentiated from other types of goiters or malignancies. Even though the thyroid is extensively involved by amyloid, patients are usually euthyroid, but many different presentations and overlaps have been reported. Currently the treatment is surgical resection of the thyroid gland Case presentation: We report a case of a 53-year-old previously healthy male who presented with a 2 year history of a progressively enlarging painless neck swelling. The patient was euthyroid and denied any associated symptoms. The patient subsequently underwent an uneventful total thyroidectomy along with an unremarkable follow up and was diagnosed with primary amyloidosis involving only the thyroid gland confirmed by histopathology. Discussion and conclusion: Amyloid goiter is a rare entity; a high index of suspicion is required in patients with an enlarging thyroid gland and a concomitant history of chronic inflammatory processes or plasma cell dyscrasia. FNA biopsy should be performed to exclude the top differential of primary thyroid malignancy. Thyroidectomy is necessary for definitive diagnosis and symptom relief. Every effort should be made to delineate the extent of the disease, and in those previously healthy plasma cell dyscrasia should be excluded Highlights: We present a rare case of amyloid goiter, detailing our work up, results and management. The majority of patients are euthyroid at presentation. Thyroid malignancy must be ruled out as a differential. Thyroidectomy is necessary to reach a definitive diagnosis and/or for symptom relief. Systemic workup required; delineating extent of disease.